Digital multimedia perception and design - Ghinea, Gheorghita; Chen, Sherry Y. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This publication provides a synopsis of the state-of-the-art technologies in perceptual-based multimedia design. It highlights how perceptual requirements can be incorporated in the design, development and transmission of multimedia, providing readers with a rich body of research and work done in this exciting area. This book aids all those interested in building true end-to-end multimedia information systems, and is useful to researchers, multimedia designers, and content and infrastructure providers